1981
DOI: 10.1038/clpt.1981.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DH/DL alleles regulating debrisoquine oxidation on phenytoin hydroxylation

Abstract: Eleven subjects of previously determined debrisoquine oxidation phenotype status (extensive metabolizer [EM], n = 5; poor metabolizer [PM], n = 6) were studied for their ability to perform the aromatic 4-hydroxylation of phenytoin. The PM subjects studied were found to be slower metabolizers of phenytoin than EM subjects in terms of the metabolite formation rate constant (kfHPPH: EM, 0.030 +/- .007 hr-1; PM, 0.016 +/- 0.003 hr-1, 2p less than 0.001) and cumulative excretion of 4-hydroxyphenytoin (48 hr after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…These unpleasant side-effects of the drug disappeared within the next 4 h. In this subject, plasma bufuralol concentrations were unusually high and carbinol concentrations low. This observation and a similar case previously reported (Balant et al, 1976) suggest a pharmacogenetic anomaly for aliphatic hydroxylation of bufuralol (Balant et al, 1978b), as recently described for alicyclic hydroxylation of debrisoquine (Mahgoub et al, 1977;Price Evans et al, 1980), N-oxidation of sparteine (Eichelbaum et al, 1979);Bertilsson et al, 1980), hydroxylation of phenytoin (Sloan et al, 1981), or other oxidated drugs (Sloan et al, 1978).…”
Section: Defective Hydroxylation Of Bufuralol Associated With Side-efsupporting
confidence: 61%
“…These unpleasant side-effects of the drug disappeared within the next 4 h. In this subject, plasma bufuralol concentrations were unusually high and carbinol concentrations low. This observation and a similar case previously reported (Balant et al, 1976) suggest a pharmacogenetic anomaly for aliphatic hydroxylation of bufuralol (Balant et al, 1978b), as recently described for alicyclic hydroxylation of debrisoquine (Mahgoub et al, 1977;Price Evans et al, 1980), N-oxidation of sparteine (Eichelbaum et al, 1979);Bertilsson et al, 1980), hydroxylation of phenytoin (Sloan et al, 1981), or other oxidated drugs (Sloan et al, 1978).…”
Section: Defective Hydroxylation Of Bufuralol Associated With Side-efsupporting
confidence: 61%
“…PM subjects have been shown to have relatively impaired abilities to metabolize phenacetin and guanoxan (Sloan et al, 1978), phenytoin (Sloan et al, 1981), sparteine (Bertilsson et al, 1980) and phenformin (Oates et al, 1982). We would advocate the use of the oxidation phenotyping procedure in the safety evaluation of both new and existing drugs where metabolic oxidation is a major determinant of the duration and intensity of a compounds pharmacological effects.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the same polymorphism controls the oxidation not only of these 2 drugs but also of other drugs, e.g. phenacetin (Idle & Smith, 1979;Ritchie et al, 1980), phenytoin (Sloan et al, 1981), phenformin (Oates et al, 1981;Wiholm et al, 1981) and nortriptyline (Mellstrom et al, 1981) (for review see Eichelbaum, 1982). Antipyrine has been used as a probe drug in studies of oxidative metabolism (Stevenson, 1977;Vesell, 1979).…”
Section: Introductionmentioning
confidence: 99%